SCN1A polymorphisms influence the antiepileptic drugs responsiveness in Jordanian epileptic patients. - Abduljabbar, Rami; Eid Tamimi, Duaa; Yousef, Al-Motassem; Mukred Saeed, Ramzi; Zawiah, Mohammed (Journal of Medical Biochemistry, 2022)
Aim: To evaluate whether the voltage-gated sodium channel alpha subunit 1 (SCN1A) gene polymorphisms influence the responsiveness of Jordanian epileptic patients to the antiepileptic drugs (AEDs). Methods: A total of 72 AEDs-treated epileptics were polymerase chain reaction (PCR)- genotyped for six single nucleotide polymorphisms (SNPs), including SCN1A rs2298771, rs3812718, rs3812719, rs2217199, rs2195144 and rs1972445. Genotype and allele distributions in drug-responsive and drug-resistant patients were compared. The six SNPs haplotypes were examined, and the linkage disequilibrium (LD) was assessed. Results: The genotypes of drug-resistant and drug-responsive groups were in Hardy-Weinberg equilibrium. Three genetic polymorphisms of the SCN1A gene seemed to influence the resistance to AEDs, on the level of alleles and genotypes. Data revealed that rs2298771 G allele, rs3812719 C allele, and rs2195144 T allele increased the risk of developing AEDs-resistance (OR=2.9; 95%CI = [1.4-5.9], p = 0.003; OR=2.4; 95%CI= [1.2- 4.7], p= 0.01; OR=2.3; 95%CI= [1.2- 4.7], p= 0.01) respectively. Haplotype analysis of SCN1A polymorphisms revealed high-degree LD that was associated with resistance to AEDs. A synergetic effect appears with highly significant association in GCCATG haplotype of rs2298771, rs3812718, rs3812719, rs2217199, rs2195144 and rs1972445 respectively (OR=2.8; 95%CI = [1.5-6.2], p = 0.002). Conclusion: Data suggests that SCN1A polymorphisms could influence the resistance to AEDs in Jordanian epileptics at three SNPs (rs2298771; rs3812719; rs2195144). Additionally, haplotype analysis indicated a strong degree of LD between the six SCN1A polymorphisms. Further investigation with a larger sample size is needed to confirm the results of the current study.